MOOSE BROWSING AND FOREST REGENERATION: A CASE STUDY IN NORTHERN NEW HAMPSHIRE - Bergeron, Daniel H; Pekins, Peter J; Jones, Henry F; Leak, William B (Lakehead University, 2011)
The impact of moose (Alces alces) browsing on the regeneration of commercial hardwood and softwood tree species was evaluated in 3 regions with different moose population densities (0.26-0.83 moose/km²) in northern New Hampshire. Regeneration surveys were conducted in 4 age classes of clear-cuts (0-5, 6-10, 11-15, and 16-20 years) in June-August 2009. Stocking rate, tree height, and damage of dominant commercial stems were measured to assess regeneration and browse damage among age classes and regions. We assumed that a stocking rate of 40-60% (stems/plot) dominant commercial tree species without severe damage was an acceptable threshold of browse damage to achieve a fully stocked stand at 80 years. Mean stocking rate of all age classes was above the threshold in all regions (47-85%); the lowest stocking rates (47-52%) occurred in the 0-5 year age class but increased thereafter in all regions. The CT Lakes region (highest moose density) had more damage than both the North and White Mountain regions in the 11-15 year age class (F = 3.05; df; 6; P = 0.0002 and 0.0058, respectively). Tree heights were lower in the CT Lakes region (F = 2.30; df; 6; P = 0.04). Most damage was restricted to a few isolated clear-cuts at higher elevation near moose wintering areas that were possibly shifting to conifer dominance. Regeneration of commercial tree species was not considered a regional problem at any moose density in northern New Hampshire.